Head motion and perception of discomfort by young children during simulated CBCT examinations - Spin-Neto, Rubens (Dentomaxillofac Radiol, 2021)
OBJECTIVES: To assess the frequency and characteristics (number, complexity, and distance) of head movements, and the perception of discomfort during simulated CBCT examinations in children, considering units with different patient positioning method and head immobilization device combinations. METHODS: Forty children (20 boys/20 girls, age range 10–14 years) were video-recorded during simulated CBCT examinations. Children were randomly allocated to a sequence of five CBCT units: Newtom-5G, Orthophos-SL, Cranex-3Dx (patient standing/sitting), and X1. The child scored his/her discomfort perception (visual scale) and the preferred/ill-favored unit. Three observers scored the videos (20% in duplicate): child movement (yes/no), number (<3/≥3/continuous), complexity (uniplanar/multiplanar) and distance (<3 mm/≥3 mm). κ statistics provided intra-/interobserver reproducibility. Severe/extreme motion was defined based on movement characteristics. Chi-square tests assessed the frequency differences of severe/extreme motion among the units, age and operator. Logistic regression analyses with severe/extreme motion as outcome were performed. RESULTS: The range of intra- and inter-observer reproducibility for movement observation was 0.78–0.89 and 0.61–0.64, respectively. Between 60% (Newtom-5G) and 100% (X1) of children moved during the examination. Severe/extreme motion was significantly related to unit and age. There was significantly less severe/extreme motion, when the child was in the supine position with a foam headrest as head support. The younger the child, the higher the risk for severe/extreme motion. The majority of the children preferred the unit with the supine position and a foam headrest. CONCLUSIONS: The prevalence of severe and extreme motion was associated with the unit’s patient positioning method and head immobilization devices combined, and child age.